IMPLICATIONS OF INDONESIAN TEA INDUSTRY INVOLVEMENT IN GLOBAL PRODUCTION NETWORK: DOWNGRADING OR UPGRADING? - Dewi Setiyaningsih (JURNAL POLINTER : KAJIAN POLITIK DAN HUBUNGAN INTERNASIONAL, 2023)
Since 21st century, the production system of capitalism has experienced rapid development with the globalization of production. The pattern of production is segmented, where a product is not only produced in one country or what is called as global production network (GPN). As a developing country, Indonesia is also involved in the GPN and create global value chain (GVC). One of the industries favored by Indonesia in the GPN is the agricultural industry. Many studies have examined the extent of Indonesia’s involvement and how the impact of Indonesia’s involvement in the GPN will be. However, not many have studied the specifics of commodities. This study examines how tea industry involvement in GPN has a social and economic impact using the framework developed by Handerson on the influence of value, power, and embeddedness on the social and economic improvement of GPN activities. Taking tea industry as a case, the results show that the industry’s involvement in the GPN can have a positive impact on development in Indonesia.